Aplikasi Pembelajaran Interaktif Augmented Reality Tata Surya Sekolah Dasar Menggunakan Metode Marker Based Tracking - Ismi Naili Qurrotul Aini; Agung Triayudi; Ira Diana Sholihati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Along with the times, the learning media also continues to grow. In solar system subjects usually, the media is used is books, where students can only see 2D forms. The purpose of this research is to build an application that can create a 3D object accompanied by an explanation, so as to make learning more interactive and easily understood using Augmented Reality (AR) technology. In previous journals, a solar system learning application has been made using AR technology, and this research will be developed by creating a quiz menu and true or false to find out how far students understand the material being taught. To ensure the application runs well, testing images, distance and angle markers, application features, and questionnaires using a black box. Marker test results can be distinguished well, markers can be detected well at a distance of 30-90 cm with an angle of 45ᴼ-90ᴼ, then questionnaires to 10 elementary school students related to this application 100% like the solar system AR application as a learning medium.